Aerodynamic Performance and Data-Driven Optimization of Flow Past an Inclined Rounded Square Cylinder (Communications in Computational Physics, 2025)
This study systematically investigates the flow characteristics around aninclined rounded square cylinder in the laminar flow regime, focusing on key influentialparameters. The simulations cover a broad parameter space, including incidence anglesfrom $0^◦$ to $45^◦,$ Reynolds numbers from 45 to 170, and corner radii from 0 to 0.4. Datafrom direct numerical simulations, including mean force and moment coefficients, rootmean square of force fluctuation coefficients, and Strouhal numbers, are meticulouslyanalyzed and divided into two datasets for model training. The developed data-drivenmodel exhibits exceptional predictive accuracy, mirroring a high-fidelity physical model.Based on this model, the optimization strategy also demonstrates notable accuracy.Specifically, the implementation of optimal design using the high-fidelity model allowsprecise control of output physical parameters, aligning them with targeted optimalconditions. This capability offers significant potential for improving the efficiency ofvarious engineering applications.